Role of Core Life Skills in Mitigating Academic Stress Among Students with Learning Disabilities - Nadaf, Zaffar Ahmad; Mrabet, Jihene; Nazir, Usma; Bashir, Saima; Behera, Santosh Kumar; Sharma, Ridhima (Journal of Ecohumanism, 2024)
The increasing prevalence of academic stress among students with learning disabilities necessitates effective interventions to enhance their well-being and academic performance. This study investigates the role of core life skills in mitigating academic stress among these students using a convergent parallel design of mixed-methods approach. Quantitative assessments revealed significant negative correlations between academic stress and key life skills such as emotional regulation, self-awareness, problem-solving, and effective communication. Qualitative insights from students, teachers, and parents highlighted themes of increased confidence, better stress management, enhanced social skills, positive behavioral changes, improved academic performance, greater independence, and emotional stability. The study underscores the importance of integrating life skills training into educational programs for students with learning disabilities. Recommendations include developing practical life skills activities, comprehensive teacher training, engaging families in the training process, and continuous evaluation and refinement of the program. These insights provide valuable guidance for educators and policymakers to reduce academic stress and improve overall educational experiences.